Hermeneutics and research methods of Social Science - Ángel Pérez, Darío Alberto (Estudios de Filosofía, 2011)
This article gives a reading of seven methodological perspectives in social sciences, from the keys of Hermeneutics: Phenomenology, Grounded Theory, Case Study, Ethnography, Participatory Action Research-IAP- Social Cartography and narrative inquiry. For each tradition, there is a general description and then a contrasting the criteria developed by the hermeneutic philosophy